Korido - Aragon, Carmina; Conception, Rowena; Garcia, Florendo R.; Jacob, Malou; Portugal, Bienvenido; Rivera, Frank; Roxas, Ma. Teresa; Tiongson, Nicanor (The Center, 1989)
A fairy tale musical play about the struggles and adventures of Filipino legendary figures using masks and puppetry.